The mediating roles of differentiation strategy and learning orientation in the relationship between entrepreneurial orientation and firm performance - Chih-Yuan Chen; Hui-Hui Huang; Shyh-Chyi Wey (交通大學, 2017)
Differentiation strategy and learning orientation are both important for entrepreneurial firms, but differ in their paths to improve entrepreneurial performance. Nonetheless, to the best of our knowledge, the differentiation strategy that mediates the relationship between entrepreneurial orientation and firm performance has not been thoroughly investigated in the literature. In addition, the mediating effect of learning orientation on the entrepreneurial orientation-performance relationship remains unclear. Therefore, this study constructs a multiple mediating model to comprehensively examine how entrepreneurial performance influences multiple firm performance measures (growth performance and profitability performance) through the mediating variables of differentiation strategy and learning orientation. This study focuses on firms in a component supply network in the automotive industry. Structural equation modelling (SEM) analysis and tests on multiple mediating effects indicate that, through the mediating effect of differentiation strategy, entrepreneurial performance increases growth performance. Moreover, through the mediating effect of learning orientation, entrepreneurial performance enhances profitability performance. The research results reveal that, in terms of the mediating effect, differentiation strategy and learning orientation can complement each other in order to raise growth performance and profitability performance, respectively.
創業導向與績效關係之研究－學習導向與策略導向之中介效果
Keywords: Entrepreneurial orientation；；Differentiation strategy；；Learning orientation；；Firm performance；；A multiple mediating model